The opera sisters : based on a true story - Monson, Marianne, 1975- (Shadow Mountain Publishing, 2022)
"Based on the true story of Ida and Louise Cook, British sisters who smuggled valuables out of 1930s Nazi Germany to finance a daring, secret operation to help Jews find hope for a new life in England"--